Identification and characterization of circular RNAs in chicken hepatocytes. (June 2019) - Zhang, Li; Xu, Haidong; Wang, Zhang; Li, Ting; Guo, Jiali; Adu-Asiamah, Patricia; Leng, Qiying; An, Lilong; Liu, Manqing; Zhang, Xiquan; Zhao, Zhihui
Abstract: CircRNAs play important roles in chicken's growth. In this context, we studied the expression profiles of circRNAs between the GHR antisense transcript overexpressed and the control groups of chicken hepatocytes by using the deep RNA-sequencing technique to identify the key circRNAs involved in chicken's growth. A total of 4772 circRNAs were detected in both groups and 92 circRNAs displayed significant differential expression between two groups. Reactome pathway analysis on the parental genes of differential circRNAs indicated that most enriched and meaningful 9 pathways were related to "Mitotic G1-G1/S-M phases", and "FGFR2c ligand binding and activation". Additionally, Five exonic circRNAs were confirmed including circGHR separated from GHR. CircGHR developed in HuaiXiang chicken from d 1 to 5 w of age and was expressed at a higher level in the nucleus than in the cytoplasm. Moreover, our results specify 5 circRNAs target sites for microRNA Let-7b that is expected to target GHR mRNA, signifying their potential role in regulating GHR gene expression in chicken. Highlights: CircRNA plays an important role in chickens growth, 4772 circRNAs including  circGHR  have been identified in the chicken hepatocyte. 92 differentially expressed circRNAs were found in GHR-AS overexpressed and control groups. Five exonic circRNAs were confirmed. Some circRNAs had the potential to function as Let-7b sponge and might form their own circRNA- Let-7b - GHR networks.